Thermoelectric plastics: from design to synthesis, processing and structure–property relationships. (7th July 2016) - Kroon, Renee; Mengistie, Desalegn Alemu; Kiefer, David; Hynynen, Jonna; Ryan, Jason D.; Yu, Liyang; Müller, Christian
Abstract : Thermoelectric plastics are a class of polymer-based materials that combine the ability to directly convert heat to electricity, and vice versa, with ease of processing. Abstract : Thermoelectric plastics are a class of polymer-based materials that combine the ability to directly convert heat to electricity, and vice versa, with ease of processing. Potential applications include waste heat recovery, spot cooling and miniature power sources for autonomous electronics. Recent progress has led to surging interest in organic thermoelectrics. This tutorial review discusses the current trends in the field with regard to the four main building blocks of thermoelectric plastics: (1) organic semiconductors and in particular conjugated polymers, (2) dopants and counterions, (3) insulating polymers, and (4) conductive fillers. The design and synthesis of conjugated polymers that promise to show good thermoelectric properties are explored, followed by an overview of relevant structure–property relationships. Doping of conjugated polymers is discussed and its interplay with processing as well as structure formation is elucidated. The use of insulating polymers as binders or matrices is proposed, which permit the adjustment of the rheological and mechanical properties of a thermoelectric plastic. Then, nanocomposites of conductive fillers such as carbon nanotubes, graphene and inorganic nanowires in a polymer matrix are introduced. A case study examines poly(3, 4-ethylenedioxythiophene) (PEDOT) based materials, which up to now have shown the most promising thermoelectric performance. Finally, a discussion of the advantages provided by bulk architectures e.g. for wearable applications highlights the unique advantages that thermoelectric plastics promise to offer.